Interpretasi Ulama tentang Signifikansi Konsep Wakaf Uang dalam Peningkatan Kesejahteraan Sosial - Ansori, Moh. Asep Zakariya; Sukendar, Egi Agustian Rahmat; Shelvira, Ersa Morita; Assyfa Ridzki Indirasari; Muhammad Azril Pebriansyah; Tirta Saepul Bahri (Economic Reviews Journal, 2024)
Cash waqf is waqf in the form of cash that can be utilized to improve the social welfare of the community. This concept has not been widely interpreted by scholars, so its significance in improving social welfare has also not been widely studied. This study uses a qualitative method with an interpretive approach. Data were analyzed using content analysis techniques to interpret scholars' understanding of the concept and significance of cash waqf. The research results show that scholars have diverse interpretations regarding the concept of cash waqf (endowment). Most scholars understand cash waqf as a form of flexibility in waqf to increase social and economic benefits for the Muslim community. The scholars also agree that cash waqf is significant for improving social welfare by expanding the scope of welfare programs that can be funded.